MCDM Application of the Third Vote - Andranik Tangian (Group Decision and Negotiation, 2021)
When choosing among alternatives, group members may have various preferences regarding the properties of a solution being sought. Since the properties partially do and partially do not meet their collective wishes, the alternatives are in fact better or worse representatives of the collective will. This idea is implemented in the so-called Third Vote election method aimed at enhancing policy representation, and we show how to use it for collective multi-criteria decision making. To be specific, we consider an example of a committee charged with naming a campus library when neither plurality vote nor Condorcet method nor Borda count gives a unique solution. The committee members have differing opinions, such as whether the library should reflect the national affiliation, be named after a great man, relate to sciences, and so forth. Balancing opinion on these issues, the proposed library names are evaluated and the optimal compromise is found.
Keywords: D71; 650; Collective multi-criteria decisions; Third Vote election method; Theory of voting